Percentage of income spent on tobacco and intention to quit: a cross-sectional analysis of the JASTIS 2020 study - Midori Takada; Takahiro Tabuchi; Hiroyasu Iso (Komiyama Printing Co. Ltd, 2022)
Background: Existing indicators for the ease of purchasing tobacco did not reflect the actual amount smoked and individual income, and did not assess heated tobacco products (HTPs). This study assessed the percentage of income spent on tobacco, including combustible cigarettes and/or HTPs, at the individual level and its relation to quit intention. Methods: An internet-based self-reported questionnaire survey was conducted in 2020 as a part of the Japan Society and New Tobacco Internet Survey. A total of 954 smokers aged 15-72 years were analyzed. We calculated the percentage of income spent on tobacco according to income levels. A high percentage implies that tobacco is not easy to purchase. The odds ratios for quit intention according to three categories of percentage of income spent on tobacco (<1%, 1-5%, >5%) were calculated by multivariable logistic regression. Results: The percentage of income spent on tobacco was higher as income level was lower, especially for dual cigarette and HTP users; the percentages in the lowest/highest income group were 7.1%/1.2% for exclusive combustible cigarette smokers; 6.5%/1.1% for exclusive HTPs users; and 9.2%/1.3% for dual users. The adjusted odds ratios (95% confidence intervals) of quit intention among the >5% of income spent on tobacco group compared with the <1% spent group were 0.43 (0.18-1.03) for exclusive combustible cigarette smokers, 0.71 (0.20-2.54) for exclusive HTPs users, and 0.11 (0.02-0.77) for dual users. Conclusions: Higher tobacco expenditure was not associated with quit intention for all categories of tobacco product users, probably due to the low price of tobacco in Japan.